Impact of earning on young children's sharing behaviour. Issue 11 (18th August 2021) - Balcı, Aslı; Kotaman, Hüseyin; Aslan, Mustafa
ABSTRACT: The purpose of the current study is to examine the impact of earning stickers compared to receiving them for free on kindergarteners' (5–6-year-old) sharing behaviours. Children's sharing behaviours were measured with the Dictator Game. Seven weeks after the first application, each child performed a matching dots to numbers activity. Thus, each child gained stickers as a result of his/her endeavour and success. The results of one-way ANOVA and logistic regression did not reveal gender, age and income as significant contributors for young children's sharing behaviours. The findings have shown that young children's sharing behaviours significantly decrease when they earn stickers rather than receive them for free without any effort. In other words, children's sharing behaviours decreased 10.4% when they were asked to share something that they had earned as a reward compared to when those rewards were just given to them for free.